Thoughts to draw upon. Issue 1 (1st March 2013) - Swartz, Amy
In our modern world filled with exacting information and result-oriented activities, drawing is both a process and product that feeds the imagination, rescues the mind from literal explanation and builds a connection between emotion and rational thought. The drawn mark can transform into a plethora of optical possibilities, creating visual poetry and free association of ideas. This article is based on my own thoughts about the mark marking process and the wide-ranging, inventive and unexpected ways students' create complex, personally relevant contemporary drawing.